Horror, Piety and Verisimilitude: Conceptual Alignments of the Greek Tragedy and the Fantastic - Oliveira Amaral, Leonardo Brandao de [UNESP]; Martins, Edson Soares (Univ Fed Minas Gerais, Fac Letras, 2022)
In addition to recognizing the permanent relevance of one of the pioneering works of studies aimed at the problem of literary creation, Aristotle's Arte Poetica (1993), this article sets out to explore points of interest and conceptual approaches between the theories of the fantastic and the Greek philosopher's text. On the way to an understanding of the picture, a comparative alignment of its similarities is proposed, in order to demonstrate the recurrence and pertinence that some critical elements assume in these two different poetic traditions. In this process, three recurrent elements can be noted in the theoretical proposals and in their objects: terror, as an effect to be achieved in the receiver; pity, as a desired relationship between the interlocutor and the reality of the characters represented; and verisimilitude, as a necessary element for the realization of the two previous effects.
Keywords: fantastic; tragedy; tragic; literary theory